Pengaruh pendidikan kesehatan reproduksi terhadap pengetahuan remaja di SMA Negeri 7 Manado - Margareth Sutjiato (UNIVERSITAS SAM RATULANGI, 2022)
The results of a survey of Indonesian health data stated that adolescent knowledge about reproductive health was not sufficient, only 33% of female adolescents and 37% of male adolescents knew that they were more likely to become pregnant if they had sexual intercourse. Adolescent knowledge about reproductive health is still relatively low. This type of research is pre-experimental in the form of one group pre-post test design. The population in this study were the students of class X who were at the State Senior High School 7 Manado totaling 45 sample respondents using purposive sampling. The results of the study on the level of knowledge before reproductive health education was carried out in the good category were 7 respondents (15.5%), the sufficient category was 23 respondents (51.1%), and the less category was 15 respondents (33.3%). And the results of the research after the reproductive health education was carried out were in the good category of 25 respondents (55.6%), sufficient category 17 respondents (37.8%), and the poor category only 3 respondents (6.7%). The results of the study showed that the level of knowledge before being given health education was (63.11%) and after being given reproductive health education was (79.00%). The result of the paired t-test test, the p value is 0.000, which is smaller than the significant value of (0.05). The conclusion is that there is a significant effect of reproductive health education on adolescent knowledge at the State 7 Manado Senior High School. Keywords: health education, reproductive health, youth knowledge